Extended Critique of the Mode of Production Theory: نقد موسّع لنظرية نمط الإنتاج - Adel Zaky, Muhammad (Journal of North African Economies, 2025)
In this article, I replace the theory of the mode of production—following a critique of its ideological foundations—with a hypothesis grounded in a critical understanding of the laws governing the movement of economic activity throughout the extensive trajectory of human social and economic development. This hypothesis posits that capitalism—understood as the subordination of a society’s economic activity to the laws governing the movement of capital—forms the foundational basis of all social systems, regardless of the degree of development of the prevailing productive forces or the form taken by the dominant relations of production. This approach enables a reinterpretation of the nature of all doctrines and the true character of those theories and systems that have emptied political economy of its social essence and stripped it of its civilizational meaning, transforming it into a tool of domination and subjugation rather than an instrument of consciousness and liberation.